P058 The lived experience of family planning of female patients diagnosed with inflammatory bowel disease and their partners during key reproductive stages: a qualitative study. (15th January 2020) - Czuber-Dochan, W; Homer, R; Brookes, M; Selinger, C; Purewal, S; Chapman, S; Steed, H
Abstract: Background: Inflammatory bowel disease (IBD) is a chronic illness affecting patients in their childbearing years. The physical effects of IBD on fertility and pregnancy in IBD in remission (e.g. disease is well controlled during conception and throughout pregnancy) are similar to the normal population. However, many women with IBD have high pregnancy-related anxieties and are more likely not to have children compared with women without IBD. The reasons cited for not having children include high levels of pregnancy-related anxieties have been insufficiently explored. The study aimed to explore the lived experience of family planning of women with inflammatory bowel disease (IBD) and their partners with or without IBD, during the reproductive stages of pre-conception, pregnancy and the postnatal period. Methods: Descriptive phenomenology was used to conduct face-to-face in-depth individual interviews. Purposive sampling was used to select participants with a maximum variation of different demographic and clinical factors, e.g. age, sex, UC/CD diagnosis, disease duration, surgery and geographic location. The NVivo 12 software programme was used to manage the data and Colaizzi's framework was utilised in thematic data analysis. Results: Twenty-four participants (21 women 11CD/10UC and three partners) were recruited from out-patient clinics (22 participants) or through the Crohn's and Colitis UK website (two participants). Women, average age 31 years old (range 27–38), were at different family planning stages: pre-conception six women (three actively planning family and three voluntarily childless); pregnant eight women and two partners; and postpartum seven women and one partner. Three women's partners, age 32–39, were recruited allowing for additional perspective of the experience being captured. In total, 19 h of interviews data were collected. Six themes were identified: (1) being diagnosed and controlling IBD symptoms, (2) relationship and family planning, (3) sources of information, (4) worries and concerns about pregnancy, (5) post pregnancy care and problems and (6) ways of improving care. Women in pre-pregnancy stage and pregnant expressed a need for more information around these themes: (1) their medication and the impact of IBD on the baby, (2) the genetic risk of passing the disease on. While pregnant and during post-partum stage, women identified a greater need for practical advice and support in relation to breastfeeding and looking after the baby. Conclusion: Information specific to family planning stages need to be provided, to help women and their partners make the informed decision about family planning. Those who decided not to go down the family route also expressed a need for counselling and support.